1996
DOI: 10.3758/bf03200883
|View full text |Cite
|
Sign up to set email alerts
|

Instability of individual differences in the association between confidence judgments and memory performance

Abstract: There are large individual differences in the degree of association between the accuracy of memories and subjective confidence in those memories. Are these differences stable within the same test, and between alternate forms of a test? In Experiment 1, college students were tested on 3 recognition memory tasks, then retested 2 weeks later on alternate forms of the same tasks. The relationship between confidence judgments and recognition performance displayed low split-half stability and low alternate-forms sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 20 publications
(20 reference statements)
2
39
0
1
Order By: Relevance
“…They found, for example, that comprehension ofwritten and oral stories correlates highly with comprehension of nonverbal picture stories. However, both Nelson (1988) and Thompson and Mason (1996) found no correlation between metacognitive accuracy scores. Moreover, Leonesio and Nelson (1990) found that performance on three distinct metacognitive tasks (EOL, JOL, and FOK) was largely uncorrelated, even for the same set of items.…”
Section: Differences In Abilitymentioning
confidence: 97%
See 2 more Smart Citations
“…They found, for example, that comprehension ofwritten and oral stories correlates highly with comprehension of nonverbal picture stories. However, both Nelson (1988) and Thompson and Mason (1996) found no correlation between metacognitive accuracy scores. Moreover, Leonesio and Nelson (1990) found that performance on three distinct metacognitive tasks (EOL, JOL, and FOK) was largely uncorrelated, even for the same set of items.…”
Section: Differences In Abilitymentioning
confidence: 97%
“…Note that the standard deviations of the FOK accuracy scores were large (.27 to .14), suggesting that these null results were not due to a restricted range ofdifficulty. Thus, the only two published studies designed specifically to test the reliability of predictions of performance for different sets of items show a complete lack of reliability (Nelson, 1988;Thompson & Mason, 1996).…”
Section: Unreliability Of Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwartz and Metcalfe pointed out further that the value of changed with the number of alternatives in a recognition test, the range of item difficulty, and the range of FOK rating. Moreover, it has been shown that the accuracy of FOK judgments (e.g., Nelson, 1988) and the confidence judgments of retrieved answers (e.g., Thompson & Mason, 1996) calculated from odd-numbered items is not correlated with that calculated …”
Section: Applications Of To Metacognitive Monitoring In Previous Studiesmentioning
confidence: 99%
“…However, it has been shown that the value of tends to be low and unstable (Glenberg & Epstein, 1987;Nelson, 1988;Thompson & Mason, 1996; for a review, see Schwartz & Metcalfe, 1994). For example, Schwartz and Metcalfe reviewed 26 FOK experiments and found that the degree of FOK accuracy measured by ranged from .03 to .50 across the experiments.…”
Section: Applications Of To Metacognitive Monitoring In Previous Studiesmentioning
confidence: 99%